Horseshoe shaped conduit design - Ahmed Amine, Lamri; Bouziane, M. T (Science des matériaux (Laboratoire LARHYSS); Vol. 7 No 01 (2016): Science des matériaux (Laboratoire LARHYSS), 2016)
In practice, the main use of the horseshoe shaped ducts is as tunnels, to design such duct the diameter and other linear dimensions are indispensables, Moreover the horseshoe duct design requires using the uniform flow fundamental relations: Darcy-Weisbach, Colebrook-White and the Reynolds number. Unlike the common implicit method used to calculate horseshoe ducts, an explicit solution is proposed in this work to design the duct with simple and direct formulas.